MODERN EDUCATION IN HIGH SCHOOL ABROAD AND KYRGYZSTAN - Babakulova R.B.; Bolot kyzy Aikerim (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2021)
The article examines modern education in higher education, analyzes the features of the didactic and structural organization of the research model of higher education in Russia and Kyrgyzstan, and has undergone a number of significant changes related primarily to the transition to a multi-level system and standardization of education.